Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Pengangguran Di Jawa Tengah Tahun 2011-2015 - PRASETYA, ANDHIKA YUDHI, Drs. Yuni Prihadi Utomo, M.M (2017)
The study was entitled "Analysis of Factors Affecting Unemployment Rate in Central Java Province Year 2011-2015". This study aims to analyze and know how big the influence of JAK, IPM, UMR and Inflation, on unemployment in Central Java in 2011-2015. The analysis tool uses panel data regression. Panel data is a mix of cross-sections covering thirty-five districts and cities in Central Java and a five-year time series - 175 observations. The results of this study show that cross section Random Effect Method (REM) is the best panel data regression model, while the time series Fixed Effect Method (FEM) is the best data panel regression model. Based on the results of the analysis found that the UMR has a significant negative effect on unemployment in cross section. While JAK has a significant negative effect on unemployment in time series.For that the government should provide a lot of training and supported policies to reduce unemployment in Central Java. Keywords: Unemployment, JAK, HDI, UMR and Inflation